Hyper IgE in Childhood Eczema and Risk of Asthma in Chinese Children - Chantel Ng; Kam Lun Hon; Jeng Sum Charmaine Kung; Nga Hin Pong; Ting-Fan Leung; Chun Kwok Wong (Molecules, 2016)
Background: Atopic eczema is a common childhood disease associated with high IgE and eosinophilia. We characterized the clinical features associated with hyper-IgE (defined as IgE > 2000 IU/L) in eczema. Methods: Nottingham Eczema Severity Score (NESS), family and personal history of atopy, skin prick test (SPT) for common food and aeroallergens, highest serum IgE ever and eosinophil counts were evaluated in 330 children eczema patients. Childhood-NESS (NESS performed at <10 years of age) and adolescent-NESS (NESS performed at >10 years of age) were further analyzed. Results: IgE correlated with NESS (spearman coefficient 0.35, p < 0.001) and eosinophil percentage (spearman coefficient 0.56, p = 0.001). Compared with IgE ≤ 2000IU/L (n = 167), patients with hyper-IgE (n = 163) were associated with male gender (p = 0.002); paternal atopy (p = 0.026); personal history of atopic rhinitis (p = 0.016); asthma (p < 0.001); dietary avoidance (p < 0.001); use of wet wrap (p < 0.001); traditional Chinese medicine use (TCM, p < 0.001); immunomodulant use (azathioprine or cyclosporine, p < 0.001); skin prick sensitization by dust mites (p < 0.001), cats (p = 0.012), dogs (p = 0.018), food (p = 0.002); eosinophilia (p < 0.001); more severe disease during childhood (p < 0.0001) and during adolescence (p < 0.0001), but not onset age of eczema or maternal atopy. Logistic regression showed that hyper-IgE was associated with personal history of asthma (exp(B) = 5.12, p = 0.002) and eczema severity during childhood and adolescence (p < 0.001). For patients <10 years of age, dust mite sensitization (p = 0.008) was associated with hyper-IgE. For patients >10years of age, food allergen sensitization was associated with hyper-IgE (p = 0.008). Conclusions: Hyper-IgE is independently associated with asthma, more severe atopy and more severe eczema during childhood and adolescence. IgE > 2000 IU/L may be a tool to aid prognostication of this chronic relapsing dermatologic disease and its progression to asthma.